Pengaruh Supervisi Pendidikan terhadap Motivasi Kerja Guru - Rizqa, Miftahir; Anggraini, Widi; Putri, Meylani Eka; Susanti, Nopalia; Elvina, Julia; Sari, Suci Rahma (MUNAQASYAH : Jurnal Ilmu Pendidikan dan Pembelajaran, 2025)
Amid the dynamics of curriculum transformation and the development of digital technology, the role of teachers is increasingly complex and challenging. High administrative workload, lack of systemic support, and formal supervision practices are the main factors in decreasing teacher work motivation. This article discusses the relationship between educational supervision practices and teacher work motivation in schools, based on literature reviews and the latest empirical data from various national institutions such as the Ministry of Education, Culture, Research, and Technology, PGRI, BPS, and research reports from INOVASI and ACDP. It was found that supervision carried out collaboratively, reflectively, and based on mentoring can increase teacher work motivation by up to 45%. In contrast, authoritarian and administrative supervision actually reduces work enthusiasm by up to 35%. This finding emphasizes the importance of reformulating educational supervision practices towards a more humanistic, participatory approach that focuses on continuous teacher professional development. Thus, improving the quality of supervision can be an effective strategy to improve teacher work motivation and the quality of learning in schools.